Sorghum elemental content response to altered nitrogen input timing and drought stress - Benjamin D. Duval; Jamie Martin; Bonnie Frey; Mark A. Marsalis (Agrosystems, Geosciences & Environment, 2025)
Abstract The nutritional and technological utility of crop biomass is dependent on tissue elemental content. We hypothesized that agronomic practices to improve semiarid crop sustainability impact element concentrations as a function of biomass response (greater biomass = more dilution of elements). Soil and sorghum (Sorghum bicolor L. Moench) tissues (postharvest roots, stems, leaves, and grain) from experimental plots with ∼40% reduction in irrigation and nitrogen (N) fertilizer timing (all at planting or split applications) were analyzed for a suite of biologically relevant elements. Irrigation and N timing interactions increased root sulfur (S) under conservation irrigation and split N, and higher cadmium (Cd) with full irrigation and single N. Significant interactions were observed for grain S, calcium (Ca), iron (Fe), copper (Cu), and molybdenum (Mo). Soils under conservation irrigation had higher sodium (Na) and lower selenium (Se) and Cd concentrations. We measured significantly greater root magnesium (Mg), Ca, vanadium (V), manganese (Mn), Fe, zinc (Zn), and strontium (Sr) under fully irrigated conditions compared to conservation irrigated conditions. Stem potassium (K) and Cd concentrations were higher under full irrigation. Leaf and grain element concentrations were not impacted by the irrigation alone. Split N applications resulted in significant increases of Na, Mg, S, K, Ca, V, Fe, Cu, Sr, Se, and Mo concentration in stems, leaves (all elements), and grain (Na, Mg, and Zn). Several nutrients declined under full irrigation and split N, previously shown to lower N2O emissions. Our results fit previous reports of significant elemental concentration variation among sorghum varieties and tissues, sorghum element concentrations respond to alterations in water and N inputs, and biomass promoting practices can decrease nutrient concentrations.